2021
DOI: 10.26434/chemrxiv.14054807
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unlocking Iminium Catalysis in Artificial Enzymes to Create a Friedel-Crafts Alkylase

Abstract: We show that the incorporation of the non-canonical amino acid para-aminophenylalanine (pAF) into the non-enzymatic protein scaffold LmrR creates a proficient and stereoselective artificial enzyme (LmrR_pAF) for the vinylogous Friedel-crafts alkylation between alpha, beta-unsaturated aldehydes and indoles. pAF acts as a catalytic residue, activating enal substrates towards conjugate addition via the formation of intermediate iminium ion species, whilst the protein scaffold provides rate acceleration and enanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…When LmrR_pAF_RGN was used to catalyse the conversion of this substrate, a similar diastereomeric ratio but different enantiomeric excesses were obtained, which may reflect the propensity of this mutant for enantioselective C-C bond formation, rather than enantioselective protonation. Similarly to our previous work, the 2-methyl substituent has a significant effect on the yields obtained, and thus products 3e-h required increased catalyst loadings and reaction times to accumulate good yields 22 . Erosion of enantiomeric excess was also observed for these products, with shorter reaction times giving higher selectivities but lower yields, and longer reaction times improving yields at the expense of selectivity.…”
Section: Table 2 Reaction Outcomes Of Competition Experiments With Equal Concentrations Of 2a and 2bsupporting
confidence: 56%
See 1 more Smart Citation
“…When LmrR_pAF_RGN was used to catalyse the conversion of this substrate, a similar diastereomeric ratio but different enantiomeric excesses were obtained, which may reflect the propensity of this mutant for enantioselective C-C bond formation, rather than enantioselective protonation. Similarly to our previous work, the 2-methyl substituent has a significant effect on the yields obtained, and thus products 3e-h required increased catalyst loadings and reaction times to accumulate good yields 22 . Erosion of enantiomeric excess was also observed for these products, with shorter reaction times giving higher selectivities but lower yields, and longer reaction times improving yields at the expense of selectivity.…”
Section: Table 2 Reaction Outcomes Of Competition Experiments With Equal Concentrations Of 2a and 2bsupporting
confidence: 56%
“…Of the many activation modes demonstrated in amino-catalysis, the electrophilic activation of enals via the formation of unsaturated iminium ions and their subsequent nucleophilic attack caught our attention due to the diversity of reaction pathways that it allows 21 . Recently we demonstrated that LmrR, with the ncAA para-aminophenyl alanine (pAF) incorporated at position 15, makes a competent and enantioselective catalyst for the Friedel-Crafts alkylation of indoles with aliphatic enal substrates, which are activated for nucleophilic attack at the β-position by iminium ion formation at the catalytic pAF residue (henceforth referred to as FC-reaction, Figure 1(a)) 22 . This transformation, which was first demonstrated with organocatalysis by Austin and MacMillan in 2002 (Figure 1(b)), creates the chiral centre during the C-C bond forming step, and thus stereoselective formation of the iminium ion and controlled approach of indole are important for good enantioselectivity 23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…Genetic code expansion has the advantage of fewer restrictions on the choice of protein scaffolds and the site therein. [27][28][29][30][31] Previously, an aniline motif has been added to the multidrug binding protein LmrR by incorporating unnatural amino acid p-azidophenylalanine followed by chemical reduction. [27][28][29][30] Whilst being less nucleophilic than pyrrolidine, 8,10 the aniline in LmrR was able to catalyze various carbonheteroatom and carbon-carbon ligation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31] Previously, an aniline motif has been added to the multidrug binding protein LmrR by incorporating unnatural amino acid p-azidophenylalanine followed by chemical reduction. [27][28][29][30] Whilst being less nucleophilic than pyrrolidine, 8,10 the aniline in LmrR was able to catalyze various carbonheteroatom and carbon-carbon ligation reactions. [27][28][29][30] Another example is the introduction of a N-methyl histidine residue into the computationally designed protein BH32; 31 subsequent laboratory evolution afforded a catalyst capable of hydrolyzing uorescein esters through formation of a covalent intermediate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation